Anomalous magnetoresistance by breaking ice rule in Bi2Ir2O7/Dy2Ti2O7 heterostructure - Zhang, Han; Xing, Chengkun; Noordhoek, Kyle; Liu, Zhaoyu; Zhao, Tianhao; Horák, Lukas; Huang, Qing; Hao, Lin; Yang, Junyi; Pandey, Shashi; Dagotto, Elbio; Jiang, Zhigang; et al. (Nature communications, 2023)
While geometrically frustrated quantum magnets host rich exotic spin states with potentials for revolutionary quantum technologies, most of them are necessarily good insulators which are difficult to be integrated with modern electrical circuit. The grand challenge is to electrically detect the emergent fluctuations and excitations by introducing charge carriers that interact with the localized spins without destroying their collective spin states. Here, we show that, by designing a Bi2Ir2O7/Dy2Ti2O7 heterostructure, the breaking of the spin-ice rule in insulating Dy2Ti2O7 leads to a charge response in the conducting Bi2Ir2O7 measured as anomalous magnetoresistance during the field-induced Kagome ice-to-saturated ice transition. The magnetoresistive anomaly also captures the characteristic angular and temperature dependence of this ice-rule-breaking transition, which has been understood as magnetic monopole condensation. These results demonstrate a novel heteroepitaxial approach for electronically probing the transition between exotic insulating spin states, laying out a blueprint for the metallization of frustrated quantum magnets.